(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
The purpose of this study is to examine the simultaneous effect of institutional ownership and major shareholder concentration on earnings quality, considering the mediating role of financial performance. Over the last decade, earnings quality has become a key indicator in assessing the reliability of financial information and investor confidence. Corporate ownership structures and shareholder concentration significantly influence managerial behavior in financial reporting and, through financial performance, affect the quality of earnings. The statistical population includes companies listed on the Tehran Stock Exchange between 2018 and 2023. Real data were collected from the CODAL system and Rahavard-Novin database. The research hypotheses were tested using the partial least squares (PLS) structural equation modeling approach. The results indicate that institutional ownership has a positive and significant effect on earnings quality, while high shareholder concentration shows a negative association. Financial performance mediates the relationship between ownership structure and earnings quality, where increases in return on assets (ROA) and return on equity (ROE) enhance the reliability of earnings. These findings emphasize the necessity of balancing institutional and major shareholder compositions to improve corporate transparency and market trust. The results are useful for regulators, auditors, and financial managers in developing effective corporate governance strategies.